MODEL JOINT ECONOMIC LOT SIZE PADA KASUS PEMASOK-PEMBELI DENGAN PERMINTAAN PROBABILISTIK - Wakhid Ahmad Jauhari; I Nyoman Pujawan; Stefanus Eko Wiratno (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2009)
In this paper we consider single vendor single buyer integrated inventory model with probabilistic demand and equal delivery lot size. The model contributes to the current literature by relaxing the deterministic demand assumption which has been used for almost all integrated inventory models. The objective is to minimize expected total costs incurred by the vendor and the buyer. We develop effective iterative procedures for finding the optimal solution. Numerical examples are used to illustrate the benefit of integration. A sensitivity analysis is performed to explore the effect of key parameters on delivery lot size, safety factor, production lot size factor and the expected total cost. The results of the numerical examples indicate that our models can achieve a significant amount of savings. Finally, we compare the results of our proposed model with a simulation model. Abstract in Bahasa Indonesia: Pada penelitian ini akan dikembangkan model gabungan pemasok-pembeli dengan permintaan probabilistik dan ukuran pengiriman sama. Pada model setiap lot pemesanan akan dikirim dalam beberapa lot pengiriman dan pemasok akan memproduksi barang dalam ukuran batch produksi yang merupakan kelipatan integer dari lot pengiriman. Dikembangkan pula suatu algoritma untuk menyelesaikan model matematis yang telah dibuat. Selain itu, pengaruh perubahan parameter terhadap perilaku model diteliti dengan analisis sensitivitas terhadap beberapa parameter kunci, seperti ukuran lot, stok pengaman dan total biaya persediaan. Pada penelitian ini juga dibuat model simulasi untuk melihat performansi model matematis pada kondisi nyata. Kata kunci: model gabungan, permintaan probabilistik, lot pengiriman, supply chain